2024
DOI: 10.3390/jcm13113277
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on High-Intensity Focused Ultrasound (HIFU) for Basal Cell Carcinoma: Effectiveness and Safety

Jacek Calik,
Natalia Sauer,
Bartosz Woźniak
et al.

Abstract: Background: The rising incidence of Basal Cell Carcinoma (BCC), especially among individuals with significant sun exposure, underscores the need for effective and minimally invasive treatment alternatives. Traditional surgical approaches, while effective, often result in notable cosmetic and functional limitations, particularly for lesions located on the face. This study explores High-Intensity Focused Ultrasound (HIFU) as a promising, non-invasive treatment option that aims to overcome these challenges, poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Importantly, this aligns with emerging evidence suggesting the benefit of incorporating advanced technologies and targeted therapies in the treatment of complex BCC cases ( 32 ). Our previous experience has demonstrated that HIFU exhibits a high success rate in completely ablating BCC lesions, with no recurrences observed during the six-month follow-up period ( 37 ). HIFU treatment is associated with minimal adverse events and superior cosmetic outcomes, significantly enhancing patient satisfaction compared to conventional treatments.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Importantly, this aligns with emerging evidence suggesting the benefit of incorporating advanced technologies and targeted therapies in the treatment of complex BCC cases ( 32 ). Our previous experience has demonstrated that HIFU exhibits a high success rate in completely ablating BCC lesions, with no recurrences observed during the six-month follow-up period ( 37 ). HIFU treatment is associated with minimal adverse events and superior cosmetic outcomes, significantly enhancing patient satisfaction compared to conventional treatments.…”
Section: Case Descriptionmentioning
confidence: 99%